The Influence of Leadership Roles and Team Building & Participation on Team Shared Mental Models: A Study of project managers in Malaysia. - Fung, Han Ping (2018)
More and more project teams are formed to achieve organizational objectives as organizations generally recognize the importance and benefits of project teams. One of the outcomes working in a project team is the proliferation of Team Shared Mental Models (TSMM). It is critical to examine the antecedents of TSMM which is the aim of this study as TSMM by itself can contribute to project team learning and others. However, it is unclear from literature whether both leadership roles and team building & participation can influence TSMM concurrently especially in a project setting study whereby there is resource and time constraint compare to normal work teams which are ongoing and operational in nature. This study has developed a research model underpinned on Cohen and Bailey’s (1997) Team Effectiveness Framework to empirically analyze how leadership roles and team building & participation can predict TSMM. Based on 201 random sample responses from project managers in Malaysia, findings suggest that leadership roles can influence TSMM indirectly via team building & participation. Knowledge contribution of this study is that project managers should invest extra efforts in team building & participation as it is the main contributor to TSMM.